2013
DOI: 10.1002/jcp.24371
|View full text |Cite
|
Sign up to set email alerts
|

Induction of STEAP4 correlates with 1,25‐dihydroxyvitamin D3 stimulation of adipogenesis in mesenchymal progenitor cells derived from human adipose tissue

Abstract: The vitamin D receptor (VDR) is expressed in human adipocytes and is transiently induced during early adipogenesis in mesenchymal progenitor cell models. VDR null mice exhibit enhanced energy expenditure and reduced adiposity even when fed high fat diets. Adipocyte-specific transgenic-expression of human VDR in mice enhances adipose tissue mass, indicating that VDR activation in adipocytes enhances lipid storage in vivo. In these studies, we conducted genomic profiling and differentiation assays in primary cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 49 publications
4
76
1
Order By: Relevance
“…Several studies have shown that STAMP2 expression is greatly induced upon adipocyte differentiation in vitro [18][19][20][21][27][28][29]. We have recently also shown that murine Stamp1 and Stamp3 mRNA expression is regulated in 3T3-L1 cells upon their adipogenic conversion [20].…”
Section: Stamp2 Expression Is Upregulated During Adipose Stem Cell DImentioning
confidence: 86%
See 1 more Smart Citation
“…Several studies have shown that STAMP2 expression is greatly induced upon adipocyte differentiation in vitro [18][19][20][21][27][28][29]. We have recently also shown that murine Stamp1 and Stamp3 mRNA expression is regulated in 3T3-L1 cells upon their adipogenic conversion [20].…”
Section: Stamp2 Expression Is Upregulated During Adipose Stem Cell DImentioning
confidence: 86%
“…STAMP2, also known as STEAP4 and tumor necrosis factor-α-induced adipose-related protein (TIARP), is up-regulated by several pro-inflammatory cytokines in both murine and human metabolic tissue [18][19][20][21][22][23][24][25][26]. In addition, STAMP2 expression is induced during adipocyte differentiation [18][19][20][21][27][28][29]. Furthermore, in vitro suppression of Stamp2 expression in 3T3-L1 cells inhibits adipogenesis [20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, while some studies have shown that the adipogenesis [24,25] continues through different mechanisms, others have focused on identifying intervention factors that can lead to weight loss, particularly, fat weight. The researchers, revealing the undetected effects of molecules driven from ATP, ADP and AMP called adenosine [26].…”
Section: Introductionmentioning
confidence: 99%
“…STEAP4 plays an important role in various functions of the human body, such as adipocyte development, metabolism, adipocyte differentiation, insulin sensitivity, and metabolic homeostasis (Zhang et al, 2008;Guo et al, 2011;Narvaez et al, 2013;Matsumoto et al, 2014). An altered expression of STEAP4 was linked with a cluster of metabolic abnormalities, such as obesity, insulin insensitivity, metabolic homeostasis, and inflammation (Chen et al, 2014).…”
mentioning
confidence: 99%
“…The expression of STEAP4 could be regulated by a variety of inflammatory cytokines, hormones, or adipokines, such as TNFa, IL-6, IL-1b, and leptin in adipocytes (Kralisch et al, 2009;Chen et al, 2010;Tanaka et al, 2012). In addition, recent studies have proved that STEAP4 plays an important role in the pathogenesis of MetS: STEAP4 primarily enhances the expression of 1,25-dihydroxy vitamin D 3 , CCAAT/enhancer binding protein alpha (C/EBPa), and peroxisome proliferator-activated receptor gamma (PPAR-c)-stimulated adipogenesis (Narvaez et al, 2013;Sikkeland and Saatcioglu, 2013). All these observations indicate that STEAP4 may be contributing to the development of MetS.…”
mentioning
confidence: 99%